Autonomous Multi-Zone Replication for Zero-Loss Settlement Systems - Raghu Gollapudi (International Journal of Computational and Experimental Science and Engineering, 2026)
Contemporary financial settlement infrastructures demand absolute data integrity across multi-zone and hybrid-cloud environments, where traditional replication strategies fail under real-world operational volatility. Zero-loss settlement systems—including national clearing networks, real-time payment rails, and high-frequency transactional platforms—face unprecedented challenges from network jitter, availability zone drift, asymmetric latency profiles, and heterogeneous infrastructure performance. Autonomous replication architectures emerge as the essential foundation for maintaining correctness guarantees in distributed financial ecosystems. These intelligent systems continuously optimize replication paths, enforce zero-loss commit governance, detect divergence through multidimensional consistency monitoring, and orchestrate sophisticated failover mechanisms. The convergence of software-defined networking paradigms, adaptive transport selection, and predictive analytics enables replication substrates to operate as self-optimizing systems aware of workload patterns, environmental risks, and latent failure conditions. Achieving external consistency at a global scale requires sophisticated timestamp management, distributed commit protocols, and dynamic adjustment of consistency levels based on application requirements. The architectural evolution toward autonomous replication represents a fundamental prerequisite for next-generation settlement infrastructure capable of operating at a planetary scale while preserving absolute correctness guarantees across expansive, heterogeneous operational environments.